Managing value proposition of small medium enterprise through digital business communication - Nur, Fasichah Tia; Andreas, Rino; Liang, Chen Wei (Manajemen Komunikasi, 2025)
Digital business communication has proven to be a determining factor in increasing the competitiveness and adaptability of SMEs in the midst of a dynamic digitalization era. In addition, the use of the Value Proposition framework in digital marketing strategies has shown significant effectiveness in expanding reach and increasing customer engagement in local product-based SMEs. This study aims to analyze how Gang Gowes implements its value proposition through strategic business communication on Instagram in the context of bicycle tourism in Solo, Indonesia. The demand for tourism, sports, and culinary experiences has grown beyond just recreation and health, but also the desire to socialize, create, upload, and share content on social media platforms, especially Instagram. This study uses a qualitative approach by analyzing Gang Gowes’ Instagram posts and conducting in-depth customer interviews. Through the BMC analysis, we found that Gang Gowes, as a bicycle rental business, implements a value proposition by differentiating itself from other similar bicycle rental business competitors. Gang Gowes offers a spontaneous experience, aesthetic value, and quick services. Furthermore, the use of interactive communication through Instagram provides interesting visualization, routes travelled, and stories built by customers that provide a value proposition to consumers effectively. This study offers a value proposition implementation model that can be replicated by tourism businesses based on experience and visual narratives, a business that can build attractiveness as well as emotional engagement with its consumers.